El modelado con arcilla para el desarrollo de la grafomotricidad en los niños del nivel inicial II de la Unidad Educativa Dr. Alfredo Pérez Guerrero, cantón Guano - Cujilema Padilla, María Fernanda (2024)
The result of the research titled "Clay modeling for the development of graphomotor skills in children of the initial level II of the Dr. Alfredo Pérez Guerrero Educational Unit Guano canton" is based on the presence of graphomotor difficulties that affect the development of writing in children due to the lack of knowledge and attendance on the part of the initial level teachers on graphomotor techniques, for which a study of theoretical bases such as graphomotor skills, its importance, the factors that influence its development and the effectiveness of modeling with clay to improve these skills. Likewise, it must be taken into account that the methodological framework of this research is constituted by a qualitative and descriptive approach, using techniques such as participant observation of 20 students and interviews with 2 teachers. The investigated population included children from the initial level II and their teachers in the Educational Unit. The results indicate that children present various graphomotor difficulties that can be effectively addressed through the use of clay modeling skills. Direct observations revealed significant improvements in the coordination and accuracy of children's graphic movements following the implementation of these skills. Therefore, the proposal consists of a guide of sculpting activities that are expected to serve to improve the graphomotor skills of the students, thus facilitating their writing learning process. The conclusion is that the activities carried out with clay They are effective tools for the development of graphomotor skills in children aged 3 to 4 years. Therefore, the regular inclusion of clay modeling activities in the educational curriculum is recommended to improve graphomotor skills and prevent future problems in literacy.